Applying filtration steps to interpret the results of whole-exome sequencing in a consanguineous population to achieve a high detection rate - Alfares, Ahmed (International Journal of Health Sciences, 2018)
Objective: Interpreting whole-exome sequencing (WES) data are challenging, requiring extensive time, and effort to review all the variants in the variant call format. Here, we examined the application of custom filters to narrow the number of candidate variants in a consanguineous population that requires further analysis. Methods: In 100 cases undergoing WES, we applied a custom filtration process to look primarily for homozygous variants in autosomal recessive (AR) disorders, and second for variants in either autosomal dominant or x-linked disorders. Results: Most identified disease-causing variants were homozygous in AR disorders. By applying our custom filtration process, we narrowed the number of candidate variants requiring further analysis to 5–15 per case while maintaining a high detection rate and completing analysis in around 45 min. Conclusion: A custom filtration process and strategy targeting a specific population provide excellent detection rates in less time and should be considered as a first-tier laboratory workflow for analysis.